Developing Vocabulary Mastery through the Use of Thematic Index Card Media among Fifth Grade Students at Al-Ikhlas Islamic Elementary School - Nyimas Siti Rofiah; Siti Uriana Rahmawati; Erta Mahyudin (Penerbit Minhaj Pustaka, 2026)
This study aims to describe the implementation of thematic index card media in teaching Arabic, analyze the challenges encountered in its application, and measure the extent to which students’ vocabulary mastery improves through this strategy. It is also expected that this research will contribute theoretically to the development of vocabulary teaching models based on constructivist theory, as well as provide practical benefits for teachers and educational institutions in improving the quality of Arabic language instruction at the elementary school level. The research method employed is Classroom Action Research (CAR), conducted in two cycles comprising the stages of planning, implementation, observation, and reflection. The research population consisted of 37 fifth-grade students at Al-Ikhlas Islamic Elementary School in the 2025/2026 academic year. Three instruments were used for data collection, namely tests, observation, and documentation. The results of the study indicate a notable improvement in students’ performance across the three stages. In the preliminary cycle, the average score was 73.2 with a mastery level of 45.95% (17 out of 37 students). This increased in the first cycle to an average score of 79.2 with a mastery level of 78.38% (29 out of 37 students). In the second cycle, the average score reached 84.7 with a mastery level of 89.19% (33 out of 37 students). Thus, it is evident that the use of thematic index card media has proven effective in improving vocabulary mastery, increasing student participation, and developing students’ ability to use vocabulary within correct Arabic sentence structures.